TANGGUNGJAWAB MASKAPAI PENERBANGAN LION AIR TERHADAP HILANGNYA BAGASI TERCATAT DALAM PERPSKETIF UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN JO PERMENHUB NOMOR 77 TAHUN 2011 (STUDI KASUS PUTUSAN NOMOR 6/PDT.G.S/ 2018/PN.DPS) - Fani Ali; Amad Sudiro (Jurnal Hukum Adigama, 2019)
Enjoying trips using the air transport fleet is one of the modes of transportation that is quite in demand because of the short travel time. However, problems sometimes arise because passenger luggage is lost or damaged during the trip resulting in passenger losses. As happened in the case of a Lion Air passenger suit for loss of baggage containing passenger luggage. The judge in his decision stipulated compensation that according to the victim was not commensurate with the total value of the loss so that the problem arose as to how the responsibilities of Lion Air flights as a carrier for the loss of belongings of passengers in baggage were recorded according to Law Number 1 of 2009 concerning flights? How to settle compensation for checked baggage lost during flight in Indonesia? This research uses normative legal research. Based on the results of the study, Lion air is responsible for the loss of luggage belonging to passengers in the checked baggage based on the provisions of Permenhub No.77 of 2011 Article 5 paragraph (1) letter a and based on the judge's decision that grants some of the plaintiff's demands that adopt a limited liability model (presumption of liability) and provide sanctions requiring compensation with a number determined by Permenhub No. 77. Settlement used in this case the plaintiff uses litigation settlement and in this case the settlement of compensation still refers to the judge's decision.